2005
DOI: 10.1038/sj.bjc.6602900
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of genetic polymorphisms (Methylenetetrahydrofolate Reductase C677T, Methionine Synthase A2756G, Thymidilate Synthase tandem repeat polymorphism) in multimodally treated oesophageal squamous cell carcinoma

Abstract: The present study retrospectively examined the correlation between the outcome of patients with locally advanced oesophageal squamous cell carcinoma (cT3-4 cN0-1 cM0) after multimodal treatment (radiochemotherapy7surgical resection), and the presence of genetic polymorphisms in genes involved in folate metabolism. In total, 68 patients who took part in a prospective multicentric trial received 5-fluorouracil (FU)-based radiochemotherapy, optionally followed by surgery. DNA was extracted from pretherapeutic tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…This may be attributable to the fact that the majority of tumour samples were retrieved from the original diagnostic block (Johnston et al, 2003). The lack of correlation between genotype and outcome in this study is similar to recent data from Sarbia et al (2006), who demonstrated that the MTHFR C677T and TS tandem repeat polymorphism had no predictive value in patients with oesophageal squamous cell carcinoma undergoing multimodality treatment.…”
Section: Discussionsupporting
confidence: 77%
“…This may be attributable to the fact that the majority of tumour samples were retrieved from the original diagnostic block (Johnston et al, 2003). The lack of correlation between genotype and outcome in this study is similar to recent data from Sarbia et al (2006), who demonstrated that the MTHFR C677T and TS tandem repeat polymorphism had no predictive value in patients with oesophageal squamous cell carcinoma undergoing multimodality treatment.…”
Section: Discussionsupporting
confidence: 77%
“…In their study, determination of TS tandem repeat provided no value in predicting the outcome of patients with locally advanced squamous cell esophageal cancer after treatment with 5-FU based chemotherapy. 58 These data are supported by the study from Nief et al in which 60 human cancer cell lines from the NCI were evaluated for three relevant TS gene polymorphisms, and no relationship was found between 5-FU cytotoxicity and TS expression or polymorphisms. 77 However, there are studies that contradict these findings and suggest that TS polymporphism status may be a useful predictor of 5-FU response.…”
Section: Discussionsupporting
confidence: 70%
“…In additional, the activity of MTHFR, folate metabolic enzyme, is also involved in the folate metabolic and DNA methylation process. As a key enzyme in folate metabolism, the product of MTHFR serves as the carbon donor for the methylation of homocysteine tomethionine, which is catalyzed by the enzyme MTR (Sarbia et al, 2006). Therefore, the MTHFR C677T may play a role in the prognosis of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%